2021
DOI: 10.5397/cise.2021.00234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-administration of atelocollagen and hyaluronic acid on rotator cuff healing

Abstract: Background: This study aimed to evaluate the co-administration effect of atelocollagen combined with hyaluronic acid (HA) injections for treatment of full-thickness rotator cuff tear (RCT).Methods: Eighty patients who underwent arthroscopic rotator cuff repair for full-thickness RCT from March 2018 to November 2019 were enrolled. The patients were randomly allocated to the following groups: combined atelocollagen and HA injection (group I, n=28), only HA injection (group II, n=26), and no injection (group III,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…2,14 Most studies reported improved clinical outcomes, especially in the VAS pain score. 2,[12][13][14][15] In the present study, intraoperative addition of atelocollagen did not improve outcome scores. However, there was slighter greater ROM.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…2,14 Most studies reported improved clinical outcomes, especially in the VAS pain score. 2,[12][13][14][15] In the present study, intraoperative addition of atelocollagen did not improve outcome scores. However, there was slighter greater ROM.…”
Section: Discussioncontrasting
confidence: 60%
“…For gel-type atelocollagen delivery, the injection is performed directly to the tear site using ultrasound in the outpatient clinics 2,15 or intraoperatively after rotator cuff repair. 12,14 Table 3 summarizes the findings of 2 level 1 randomized controlled trials that reported on clinical applications of atelocollagen. 12,15 Using gel-type atelocollagen injection, Jeong et al 12 observed an additional effect after coinjection of atelocollagen and hyaluronic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotator cuff tears are a common clinical problem with multifactorial etiology including degenerative changes and trauma. A commonly accepted and widely used treatment approach for rotator cuff tears involves arthroscopic repair [1][2][3] . Although most patients experience satisfactory clinical outcomes after arthroscopic rotator cuff repair (ARCR), potential complications have also been reported from a number of studies [4][5][6][7] .…”
mentioning
confidence: 99%
“…향상을 통해서 부분파열 및 회전 근개 건병증의 치료에 PRP 주사, 증식치료(prolotherapy) 나 polydeoxyribonucleotide 주사, atelocollagen 주사[25] 등 재생치료가 시도되고 있다. 또한 혈소판에 풍부한 성장인 자를 손상이 있는 부분에 투여하여 생체의 치유능력을 향상 을 통해 조직의 치유를 기대해 볼 수 있으며, 최근 연구에 따 르면 PRP가 건침에 비하여 회전근개의 치유를 위한 성장인 자를 모이게 하며[12], 스테로이드 주사만큼 통증 조절에 효 과적이라는 보고가 있다[26].…”
unclassified